Faktor-Faktor Yang Berhubungan dengan Kecelakaan Kerja pada Pekerja Pembangunan Gedung di Kecamatan Telanaipura Kota Jambi Tahun 2022 - Putri Wulandari; Cici Wuni; Sugiarto Sugiarto (Yayasan Literasi Sains Indonesia, 2023)
Construction is an industrial sector with work sites that are mobile, open and influenced by weather, limited implementation time, and very limited worker capabilities. The accident that occurred in the construction of a building in Telanaipura District was scratches caused by work tools or materials, cut off by work tools, and even fell from a height which caused workers to break their legs/hands. The purpose of this study is to determine the factors related to work accidents in building construction project workers in Telanaipura District in 2022. This study used a Cross Sectional design. The sample in this study was 67 people, the instruments in this study used questionnaires, and the analysis used was univariate and bivariate analysis using the chi-square test. Based on the results of a study of 67 respondents, as many as 40 people (59.7%) had experienced accidents, as many as 39 people (58.2%) committed unsafe actions, as many as 30 people (44.8%) had less knowledge, and as many as 45 people (67.2%) experienced fatigue. There is a relationship of unsafe action with work accidents with a p-value (0.008). There is no knowledge relationship with the accident with the p-value (0.072). There is a relationship between fatigue and work accidents with a p-value (0.014). It is recommended for workers to cooperate with each other by reminding each other about unsafe actions taken while working, as well as continuing to use personal protective equipment according to the type of danger in the workplace.